Emerging applications of differential equations and game theory - Alparslan-Gok, Sirma Zeynep, 1980-; Aruǧaslan C̦inc̦in, Duygu, 1979- (Advances in computer and electrical engineering (ACEE) book series., 2020)
"This book examines interdisciplinary applications of differential equations and game theory"--